Putting the ‘love back in’ to journalism: Transforming habitus in Aboriginal affairs student reporting - Mason, B.; Thomson, Chris; Bennett, D.; Johnston, M. (2016)
While journalism scholars have identified a lack of critical reflexivity in journalism, few have identified ways to educate university students for critically reflexive journalism practice. This article reports on a university teaching project that enables such practice as a means to counter exclusions, stereotyping and misrepresentation of Aboriginal people by large-scale Australian media. Using Bourdieu’s concept of habitus to track transformations in student dispositions, particularly as they relate to practice, the article shows how participating students became more competent and confident Aboriginal affairs journalists with a strengthened sense of themselves, their practice and the journalistic field. Their investment in the field was strengthened as they sought to tell hidden and disregarded stories, and to include previously excluded voices, perspectives and representations. The article describes and analyses an example of critically reflexive learning, practice and teaching that has the potential to transform students’ learning, the journalistic field and relations between Aboriginal non-Aboriginal Australians.